A quantitative approach to histopathological dissection of elastin‐related disorders using multiphoton microscopy. (10th October 2013) - Tong, P.L.; Qin, J.; Cooper, C.L.; Lowe, P.M.; Murrell, D.F.; Kossard, S.; Ng, L.G.; Roediger, B.; Weninger, W.; Haass, N.K.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Multiphoton microscopy has been used on tissue sections and in patients to assess skin pathologies. Autofluorescent structures within the skin, including elastic fibres, can be visualized using multiphoton imaging without the need for histochemical or antibody staining. What does this study add? Development of the Dermal Elastin Morphology Index (DEMI) to enable objective three‐dimensional quantification of elastic fibres. Use of DEMI is demonstrated in elastin‐related skin disorders. DEMI can be used on tissue sections, where it correlates with histopathology, but in contrast to histopathology it allows in vivo application.